Green human resource management practices in the manufacturing industry: A sustainable approach - Ichdan, Dany Amrul; Maryani, Maryani (Goodwood Publishing, 2024)
Purpose: This study investigates the adoption of environmentally friendly Human Resource Management (HRM) practices as a sustainable strategy in the manufacturing sector. It focuses on how employees' environmental consciousness, environmental regulations, and companies’ environmental performance impact the implementation of green HRM practices. Research Methodology: The study involved surveying employees and managers in manufacturing companies, with data gathered and analyzed quantitatively. Results: The findings indicate that Employees’ environmental awareness significantly influences the adoption of green HR practices, whereas the effect of environmental regulations is relatively positive. Furthermore, a company’s environmental performance was found to be positively correlated with its green HR practices. Limitations: This was a survey-based study. Further qualitative studies should be conducted to improve the quality of results. Contribution: Suggestions for future research include conducting further studies to comprehend the internal and external factors influencing the adoption of green HR practices and considering the role of organizational culture and individual motivation in promoting such practices. This will provide a more comprehensive understanding of green HR strategies, which can assist manufacturing companies in achieving enhanced environmental sustainability.